Selected principles of social welfare in the Polish and German legal systems - Sierpowska, Iwona (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
Social assistance is a part of the social security system. In Poland and Germany, it is regarded as the ultimate form of social support for people who are not entitled to benefits from social security and other forms of social support. There are several similarities between Polish and German social assistance law as both social security systems belong to the conservative model of social policy. Many analogies relate to the principles for granting social assistance. A special role here should be attributed to subsidiarity, whose plurality includes not only a place in the social security system but also in the division of public and social tasks, cooperation with authorities, social organizations as well as self-help and mobilization of beneficiaries. Therefore, it will not be an exaggeration to claim that it is the principle of subsidiarity that is the source of social assistance and the determinant of its objectives.
Keywords: pomoc społeczna; polski system prawny; niemiecki system prawny